ChemInform Abstract: Selective Catalytic Synthesis Using the Combination of Carbon Dioxide and Hydrogen: Catalytic Chess at the Interface of Energy and Chemistry. Issue 32 (22nd July 2016) - Klankermayer, Juergen; Wesselbaum, Sebastian; Beydoun, Kassem; Leitner, Walter
Abstract: Review: [253 refs.